Reactive Programming Paradigm for Development User Intrfaces - Bulgakova, O.S.; Zosimov, V.V. (Control systems & computers, 2019)
The article discusses the relevance of using the paradigm for user interfaces development. The essence of the reactive programming paradigm, its features and disadvantages are described. The technology of reactive programming ReactiveX is considered. Features of the reactive systems implementation are described as a result of an in-depth study of the main development tools and language structures. The reactive paradigm possibilities of reducing labor costs for building valid models, minimizing errors, and efficient and quick solution of the tasks are shown on the example of the application implementation.